What hinders and what motivates parents’ engagement in school? - Bouakaz, Laid; Persson, Sven (International Journal about Parents in Education, 2023)
In this paper we discuss what hinders and what promotes parental involvement in regular school, on account of the supplementary school which children attend alongside their regular school education. The main study lasted from autumn term 2002 to spring term 2004. A home-school mediation project was established in an urban school in Sweden to promote parental involvement. Here we will present the part of the study which is concerned with supplementary schools. The questions to be discussed in this paper are: is there a mutual distrust between parents and school, what motivates the parents to be engaged in supplementary schools and what hinders them from directing their engagement to the regular school? First we discuss trust and distrust between parents and teachers, secondly, on account of the answer to the question addressed, we try to understand why the parents put their energy and hope to supplementary schools.